2012
DOI: 10.1002/elps.201100693
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent iridium(III) complexes as novel protein staining agents

Abstract: This article reports a new class of luminescent metal complexes, biscyclometalated iridium(III) complexes with an ancillary bathophenanthroline disulfonate ligand, for staining protein bands that are separated by electrophoresis. The performances of these novel staining agents have been studied in comparison with tris(bathophenanthroline disulfonate) ruthenium(II) tetrasodium salt (i.e. RuBPS) using a commercially available imaging system. The staining agents showed different limits of detection, linear dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…Silver nitrate staining is also sensitive to a number of external factors such as the temperature and the development time making the Coomassie brilliant blue staining the preferred staining for proteomics. It is also possible to stain the proteins by using organic fluorescent dyes (such as Deep Purple TM , a fluorescent dye based upon the natural compound epicocconone, originally isolated from the fungus Epicoccum nigrum [ 30 ], Flamingo TM (Bio-Rad) and Krypton TM (Pierce) and metal complex or metal chelates dyes (such as SYPRO Red and Orange [ 31 ], the well-known being SYPRO Ruby [ 32 ], RuBPS [ 33 ], ASCQ_Ru [ 34 ]) and IrBPS [ 35 ]). This fluorescent staining is sensitive (ng to pg level), non-covalent (or reversible for epicocconone) and, consequently, compatible to MS.…”
Section: In-gel Quantification Of Proteinsmentioning
confidence: 99%
“…Silver nitrate staining is also sensitive to a number of external factors such as the temperature and the development time making the Coomassie brilliant blue staining the preferred staining for proteomics. It is also possible to stain the proteins by using organic fluorescent dyes (such as Deep Purple TM , a fluorescent dye based upon the natural compound epicocconone, originally isolated from the fungus Epicoccum nigrum [ 30 ], Flamingo TM (Bio-Rad) and Krypton TM (Pierce) and metal complex or metal chelates dyes (such as SYPRO Red and Orange [ 31 ], the well-known being SYPRO Ruby [ 32 ], RuBPS [ 33 ], ASCQ_Ru [ 34 ]) and IrBPS [ 35 ]). This fluorescent staining is sensitive (ng to pg level), non-covalent (or reversible for epicocconone) and, consequently, compatible to MS.…”
Section: In-gel Quantification Of Proteinsmentioning
confidence: 99%
“…3,4 The structure of RuBPS has inspired the successive development of BPS-based Ir(III) cyclometalated complexes with the general formula [Ir(C^N) 2 (BPS)], in which the peculiar and intense luminescent output of this class of metal complexes was combined with the "usual" protein recognition properties displayed by the sulfonate groups. 5 In these regards, it is worth noting that a recent report by Zhou and coworkers showed that also cationic and neutrally charged Ir(III) cyclometalated complexes devoid of any -SO 3 moieties could also be used as protein staining agents, pointing to the importance of other factors aside of electrostatic interactions in determining the performances of protein stains. 6 To the best of our knowledge, no examples of fac-triscarbonyl Re(I) diimines, one of the most extensively studied classes of luminescent d 6 metal complexes, have been considered for the specific purpose of protein staining.…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of this work, 15,17 these and other bis-cyclometalated iridium complexes containing an ancillary BPS ligand ( Fig. 1a; 1-4) have been utilised for a variety of luminescence-based applications 5,12,[22][23][24] and they are now commercially available.…”
Section: Introductionmentioning
confidence: 99%